Addressing normative constraints, crucial for designing gender-transformative approaches - Awinoh, Martha; Ngugi, Elphas (CGIAR, 2024)
Discriminatory social institutions serve as key drivers of numerous challenges in Tanzania and Nigeria. Steve Cole, lead of HER+ TRANSFORM work package sheds light on an innovative framework designed to investigate normative constraints to gender equality in agrifood systems.